Desenvolvimento de um ELISA de bloqueio para o diagnóstico da neosporose bovina - Sinnott, Francine Alves (2014)
Neosporosis is a disease caused by the obligate intracellular parasite Neospora caninum, causing reproductive disorders, such abortions and sltillbirths in several animals, being considered a major cause of abortion in cattle worldwide. The serological standard diagnosis is indirect fluorescent-antibody test (IFAT), but due to morphological and antigenic similarities of N. caninum with other protozoa of the phylum Apicomplexa, such as Toxoplasma gondii and Sarcocystis spp., false positive results may occur. To improve the diagnosis of this disease and reduce cross-reactions with other coccidian, the use of specific recombinant proteins of N. caninum has been described. The Nc-p43 surface protein encoded by the gene NcSRS2 is specific of the parasite and is present in tachyzoites and bradyzoites of N. caninum. Indirect ELISA format assays have been developed for the diagnosis of neosporosis, however the blocking ELISA may present additional level of specificity. In this context, the objective of this study was develop and standardize a blocking ELISA (b-ELISA) for the diagnosis of bovine neosporosis. To this end, NcSRS2 gene, previously cloned into plasmid vector, was used to produce the recombinant protein (rNc-p43) in prokaryotic expression system Escherichia coli. The purified protein was used to produce a polyclonal antibody (pAb/rNc-p43) in rabbit and this was further purified and characterized by indirect ELISA. For the development of the b-ELISA were used a total of 152 cattle sera (71 negative and 81 positive) and 10 positive cattle sera for toxoplasmosis, all previously confirmed by IFI. As controls, a pool of all positive sera and a pool of all negative sera were used, in addition to a normal calf serum, confirmed by IFAT, used with negative reference sera. The percent inhibition for each sample was determined by comparing the optical density (OD) mean of test sera to the OD mean of negative reference sera. The cut-off value was determined as the percent inhibition of negative pool. The results suggest that the b-ELISA is a tool that can be used for diagnosis of bovine neosporosis, with a sensitivity of 98.7% and specificity of 88.7% when compared with the IFAT. Antibodies against T. gondii present in positive samples for toxoplasmosis were not able to recognize the rNc-p43. The b-ELISA showed that serum samples positive for N. caninum is able to prevent the binding of pAb/rNc-p43, enabling detect different class of antibodies in a single assay. This technique is